2023
DOI: 10.1111/ijfs.16790
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different edible oils on in vitro starch digestibility and physical properties of rice starch and rice flour

Jukkrapong Pinyo,
Rungtiwa Wongsagonsup,
Natrapee Panthong
et al.

Abstract: SummaryAmylose has the ability to form inclusion complexes with lipids and is resistant to enzymatic hydrolysis. This research aimed to explore the impacts of different healthy edible oils, i.e., coconut oil (CO), rice bran oil (RO), palm oil (PO), and soybean oil (SO) on the in vitro starch digestibility and physical properties of rice starch and rice flour. Each edible oil (10% w/w) was transferred to rice starch and rice flour and cooked at 95 °C for 8 min. The contents of rapidly digestible starch and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…While the cellulose content of control samples produced using rice flour was determined to be the lowest, the starch content was identified as the highest. Pinyo et al (2024) reported in their study that rice flour has a high starch content [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…While the cellulose content of control samples produced using rice flour was determined to be the lowest, the starch content was identified as the highest. Pinyo et al (2024) reported in their study that rice flour has a high starch content [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The amylose-lipid complex is resistant to enzymatic hydrolysis and has been proposed as a new source of resistant starch (type 5) [ 17 ]. Palm oil and coconut oil, as edible oils with a high content of saturated fatty acids, promote the formation of a stable amylose-lipid complex in the form of a single-helical inclusion complex, which limits the starch digestibility of cooked rice starch and rice flour [ 18 ]. These oils are also said to have various health benefits, such as reducing visceral adiposity and plasma glucose levels and lowering cholesterol levels [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%